Platformalism: Finding the Forms of Platform Literature - Cox, George (2021)
In this thesis, I identify platform literature as an emergent genre of the third generation of electronic literature. Platform literature is multimodal and devised for, published on and distributed through pre-existing and proprietary online platforms. The architecture and features of these platforms heavily influence both the form and content of platform literature: for instance, the 280 characters of the tweet, the moments of engagement in an interactive film on Netflix, and the participatory comments section of a YouTube video. However, despite the relatively recent emergence of platform literature, the genre bears clear resemblances to print precursors, continuing and innovating upon the forms of these analogue antecedents.